Persepsi Masyarakat Terhadap Proses Pembentukan Undang-Undang yang Tergesa-Gesa, Studi Kasus: (Undang-Undang Kontroversial Di Jalan William Iskandar Pasar V, Kab. Deli Serdang, Sumatra Utara) - Seven Rius Laia; Parlauangan Gabriel Siahaan; Novridah Reanti Purba; Narach Larasati Nasution; Imelda Malona Tarigan; Ferdy Akbar; Aril sharon Saragih (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
The law-making process in Indonesia should ideally reflect the principles of transparency, public participation, and accountability. However, in practice, it is often found that legislation is enacted hastily without adequate involvement of the public. This situation causes public unrest, triggers a crisis of legal legitimacy, and diminishes trust in legislative institutions. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The number of respondents involved in this study is 5. The aim of this research is to explore public perceptions of the hasty law-making process and its impact on public trust and legal legitimacy. The findings of this study are expected to provide valuable input for policymakers to improve the legislative mechanism to be more participatory and transparent. The results of the study show that the majority of people in Jalan William Iskandar Pasar V, Deli Serdang, Sumatra Utara Regency, have a negative perception of the hasty and non-transparent legislative process. They feel excluded, lack access to information, and believe that the laws created do not reflect the aspirations of the public. This research concludes that the legitimacy crisis arises due to the lack of participation and transparency, and therefore, it is recommended that future legislative processes be more inclusive, fair, and aligned with the principles of participatory democracy